OBSTACLES IN LEARNING TO SPEAK ENGLISH FACED BY NURSE STUDENTS OF STIKES SANTU PAULUS RUTENG, FLORES - Daar, Gabriel Fredi (Fakultas Ilmu Kesehatan dan Pertanian Unika Santu Paulus Ruteng, 2016)
Learning English is now seen as a need for expanding career, improving personal quality (speaking ability) and taking part in the world competition. For the sake of improving English speaking capability, many learning strategies are chosen. However, learning to speak English is not an easy task. Difficulties and problems are found during the efforts even reducing learning motivation. This research is aimed at investigating the obstacles encountered by nurse students in learning to speak English. It is a qualitative research conducted at students of Nursing Study Program STIKes St. Paulus Ruteng. The research subject is determined purposively, and the data collection is done using interview technique, observation and documentation. The findings indicated that the obstacles faced by the nurse students were classified into four categories .The obstacles included problems dealing with students interest of learning English, students learning motivation, students self-confident to start speaking, and basic knowledge of English and vocabulary mastery. The comments made by the students could be considered by the school authorities in order to improve quality of education for nurse students during the learning process